Management of Guidance and Counselling Program at Inclusive Elementary School - Muhamad Irham (Program Studi BKPI IAIN Salatiga, 2022)
Guidance and Counselling program is designed to achieve student independence. It is focused on assisting students’ potential development and solving their problems. In fact, the implementation of this program at the inclusive elementary schools does not yet have standard guidelines and rules. Therefore, this study was aimed to obtain an overview of the guidance and counselling management model in Al-Irsyad Al-Islamiyyah Elementary School in Purwokerto as an inclusive elementary school. This research was a qualitative research with a case study approach. The research subjects were teachers at Al-Irsyad Elementary School. Data was collected through interviews, questionnaires, observation, and documentation. The results of the study shows that: 1) Al-Irsyad Al-Islamiyyah Elementary School has provided the guidance and counselling program, 2) Guidance and Counselling program at Al-Irsyad Al-Islamiyyah Elementary School carry out the functions of this program which include leadership, planning, organizing, implementing, monitoring, evaluating, reporting and doing follow-up program, and 3) The guidance and counselling management model developed is the Integrated Comprehensive guidance and counselling management based on Islamic values. Thus, Al-Irsyad Al-Islamiyyah Elementary School in Purwokerto as an Inclusive Elementary School has organized comprehensive guidance and counselling services that can be used as a reference in providing such program at Inclusive Schools.